Converging resources and co-producing for innovation: evidence from healthcare services. Issue 3 (30th July 2019) - Sehgal, Sanjeewani; Gupta, Garima
Abstract : Purpose: The purpose of this paper is to examine healthcare organizations for the improvements in their existing services (incremental innovation) as well as for the new service developments (radical innovation) initiated through the utilization of resources and co-producing behavior. Design/methodology/approach: The paper uses an SEM approach to analyze the responses obtained from 257 medical administrators of 50 hospitals registered with National Accreditation Board for Hospitals and Healthcare Providers. Findings: The results reflect a positive and significant impact that is more driven by internal resources and is found to be stronger for incremental innovation in healthcare. The study also posits that resource utilization in conjunction with co-production activities has greater potential to bring innovation that is likely to succeed and stay inimitable. Research limitations/implications: The paper outlines scope for future research and suggests inclusion of other service sectors, geographical locations and performance indicators to attain a better understanding of the constructs examined. Practical implications: The paper outlines implications for policy makers concerned with healthcare. Providers of health services ought to develop a proactive customer-oriented approach so as to deliver value through service innovations. Integrating customer co-production processes may further augment the overall quality of care. Originality/value: Empirical studies integrating the resource-oriented view of innovation along with firms' co-production and collaborative mechanisms are majorly lacking. The study bridges this gap and suggests ways to bring innovation in health services, a pivotal need for health institutions of an emerging economy like India.